Request for conﬁrmation concerning valuation for cutting rebar of foundation piles - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request for conﬁrmation concerning valuation for cutting rebar of foundation piles of BRACU new campus development project.